The Urgency of Developing Teaching Modules Based on Ethnomatics Learning for Numeracy Skills - Fitriani, Fitriani; Baharuddin, Muhammad Rusli; Patmaniar, Patmaniar; Wafda, Andi (Universitas Muhammadiyah Mataram, 2025)
Numeracy is one of the essential foundational skills that students must master, yet the 2018 Programme for International Student Assessment (PISA) survey revealed that Indonesian students ranked 72nd out of 79 countries in numeracy skills, reflecting low mathematical literacy globally. This issue often stems from the presentation of mathematical material that is abstract and less relevant to everyday life contexts. This study aims to develop a teaching module based on ethnomathematics learning that integrates the local culture of Luwu to improve students' numeracy skills. This research employs the research and development (R&D) method with the 4D model, encompassing the stages of Define, Design, Develop, and Disseminate. In the Define stage, a needs analysis and identification of local cultural potential were conducted. In the Develop stage, the module was validated by experts using validation sheets to assess the relevance of the material, completeness of information, and clarity of presentation. The module's practicality was evaluated through questionnaires and observations to assess its ease of use and effectiveness in learning. The results indicate that the teaching module based on ethnomathematics learning is both valid and practical. The module achieved high validity based on expert assessments covering material relevance, completeness of information, and clarity of presentation. The module's practicality was measured through teacher and student responses, reflecting its ease of use and effectiveness in enhancing student engagement in numeracy learning. In conclusion, the teaching module based on ethnomathematics learning has proven effective in improving students' numeracy skills and successfully integrating local cultural values into learning. This study contributes to the development of relevant, meaningful, and contextual teaching materials in mathematics education.